Comparison of Reversal Test Pictures among Three Groups of Students: Normal, Education Mental Retarded and Students with Learning Disabilities in Tehran - Mohammad Reza Koushesh; Hadi Bahrami; Akbar Biglarian; Akbr Forougheddin-A'dl; Laleh Same-Siahkalroudi; Hamid Reza Karimi (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: Riversal visual perception discrimination test is one of the dyslexia diagnostic tests in children which can be performed in the group (group-based) and it is reliable to detect these disorders in students of the primary schools especially those who spend their first educational weeks or months. The aim of this survey is comparison of Riversal test pictures among three groups of students: normal, educable mental retarded students and students with learning disabilities, aged 8-12 years old that were under coverage of Tehran Welfare Department. Materials & Methods: This Comparative cross - sectional study has performed on 150 girls and boys of mentioned groups that were selected by simple randomize selection. Results: The findings suggested that there was significant difference between surveyed groups (P=0.001). The highest scores were related to normal students and the lowest scores to educable mental retarded. The interval of negative scores of educable mental retarded from normal students was more than that of between educable mental retarded and learning disabilities. Conclusion: This survey indicates that students with learning disabilities (dyslexia) have problems in their visual perception and this test can help to diagnose and determine abnormal children as soon as possible in order to better treatment.